ANALISIS DESKRIPTIF KEPUASAN KERJA, PERILAKU KEWARGAAN ORGANISASIONAL, KOMITMEN ORGANISASIONAL KARYAWAN GMC HEALTH CENTER UGM TAHUN 2014 - RIJANTO, RIJANTO ([Yogyakarta] : Universitas Gadjah Mada, 2015)
GMC Health Centeris a business entitythat isestablishedby Universitas Gadjah Mada. Engangedin the health service for student sandemployeesof UGM, GMC Health Centere stablishedby the Rector Decree Number51/J01/KP/2000, dated 22May 2000.GMC Health Centeris locatedat Bulaksumur BlokH No.6 Yogyakarta. With the establishment of GMC, students who would like to checktheir health only need to submit thestudentscard andthey have beendirectlyaddressedby theofficers/employeesandphysiciansof GMCHealthCenter. Thisstudyaims to determinejob satisfaction, organizational citizenship behavior, andorganizational commitmentof employeesof GMC HealthCenter, UniversitasGadjahMada. The research was conductedinJuly 2014. Thesubject of the researchwas takenby using purposivesampling, they wereemployeeswho servedin theservicedesk orwhose dutiesdirectlyrelated to thestudents. The number of sampleswhichqualifywere 50people. A questionnairewas used as data collection instrumentwith a5-point Likertscale, whichhas beentestedfor validity and reliability. Data were analyzed using descriptive method. The results of the study revealed: (1) the job satisfactionof employeesof GMC HealthCenterclassifiedas satisfied(meanscore=3.68)